Pengaruh Berat Weight Roller Terhadap Daya, Torsi, dan Topspeed pada Honda Beat - Resdianto , Agus; Hermawan, Dadang; Farid, Akhmad (Widyagama University of Malang, 2024)
CVT (Continuous Variable Transmission) components have several components that must be considered, one of which is the roller component that is often used on the 2013 Beat automatic motorbike. The rollers found on automatic motorbikes consist of two types. The rollers have different masses on both parts. Based on the mass of the two types of rollers, a study was conducted using the experimental method, which is a form of study to find cause and effect (causal relationship) between two factors by eliminating or reducing or setting aside other interfering factors. The study was conducted to determine the effect of replacing the roller with a mass of 15 grams on power, torque and top speed on the 2013 Honda Beat motorbike. The testing tool used in this study used a dynamometer that was able to analyze the effect of roller mass on the power generated by the automatic motorbike and also the centrifugal force of the roller. The lighter the roller weight, the smaller the centrifugal force generated. However, at high engine speeds, centrifugal force will decrease faster than rollers that have a heavier weight. The torque obtained in the use of 13 gram and 15 gram rollers respectively is 9.24 Nm, 8.79 Nm obtained at 6000 rpm engine speed. While the top speed obtained from the use of 13 gram roller is 75.06 km / h in 1 second, and the top speed achieved by the 15 gram roller is 78.65 km / h in 1 second.